1997
DOI: 10.1007/s11746-997-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

Frying quality and oxidative stability of high‐oleic corn oils

Abstract: To determine the frying stability of corn oils that are genetically modified to contain 65% oleic acid, high-oleic corn oil was evaluated in room odor tests and by total polar compound analysis. Flavor characteristics of french-fried potatoes, prepared in the oil, were also evaluated by trained analytical sensory panelists. In comparison to normal corn oil, hydrogenated corn oil and high-oleic (80 and 90%) sunflower oils, high-oleic corn oil had significantly (P < 0.05) lower total polar compound levels after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 23 publications
7
86
1
2
Order By: Relevance
“…Tables I and II show an increase of the transoleic acid (elaidic acid) content in both oils due to frying, which results in thermal oxidation (Kiritsakis et al, 1989;Warner y Knowlton, 1997;Cuesta y Sánchez-Muniz, 1998;Pantzaris, 1998). Trans-oleic Vol.…”
Section: Trans Oleic Acid (Elaidic)mentioning
confidence: 99%
“…Tables I and II show an increase of the transoleic acid (elaidic acid) content in both oils due to frying, which results in thermal oxidation (Kiritsakis et al, 1989;Warner y Knowlton, 1997;Cuesta y Sánchez-Muniz, 1998;Pantzaris, 1998). Trans-oleic Vol.…”
Section: Trans Oleic Acid (Elaidic)mentioning
confidence: 99%
“…190 o C w wysokooleinowym oleju kukurydzianym znajdowało się znacząco mniej związków polarnych niż w uwodornionym oleju kukurydzianym. Warner i Knowlton [49] zaobserwowali również, że olej kukurydziany konwencjonalny oraz uwodorniony charakteryzowały się niższą jakością sensoryczną oraz stabilnością oksydacyjną w porównaniu z olejem kukurydzianym wysokooleinowym po 17,5 h smażenia frytek w 190 °C.…”
Section: Właściwości Tłuszczów Wysokooleinowychunclassified
“…However, minor components exerting antioxidative or prooxidative action also contribute to oil performance. In this regard, different reports have shown that oils clearly differing in their degree of unsaturation exhibited similar behavior at high temperatures (Márquez-Ruiz et al, 1995;Warner and Knowlton, 1997;Norman et al, 2003;Norman et al, 2006).…”
Section: Introductionmentioning
confidence: 97%